What is Living in Deep Ecology? - Clark, John P. (The Trumpeter, 2015)
This article asks what in deep ecology has the most enduring value, what escapes typical forms of negative criticism, what contributes most to the development of ecological thought, and what shows the most promise of transforming the larger society into an ecological one. Such exemplary qualities are discovered in Gary Snyder’s reflections on the wild and the sacred, Arne’s Naess’s inquiry into the meaning of “free nature,” Thomas Berry’s depiction of the place of humanity in the Earth Story and the Universe Story, and Delores LaChapelle’s exploration of the ethos and spirituality of place. It is found that a focus on such dimensions of deep ecological thought can reveal points of interconnection between what have been called “radical ecologies,” and help guide us in the direction of the deep logos of the oikos.